P‐129: Estimating Non‐radiative Decay Rates in TADF Emitters Using Steady‐State and Transient Optical Data. Issue 1 (28th June 2022) - Sem, Stefano; Jenatsch, Sandra; Stavrou, Kleitos; Danos, Andrew; Monkman, Andy P.; Ruhstaller, Beat
Abstract : In this study we describe a new method to determine non‐radiative decay rates in TADF emitters using transient and steady‐state optical measurements. A global fitting algorithm is designed and applied to estimate the entire set of decay rates involved in typical TADF emitters.